(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article examines the linguistic features of pharmacodynamic descriptions of five pharmaceutical drugs from various pharmacological groups: antimetabolites, herbal remedies, cytokines, hormonal agents, and protein kinase inhibitors. A quantitative analysis of the official instructions reveals the frequency of borrowed terminology, common syntactic structures, and distinctive lexical characteristics. The study highlights both general and group-specific traits of pharmaceutical discourse.